Pengaruh Earnings per Share, Return on Equity, Price to Book Value, dan Total Arus Kas Terhadap Harga Saham - Eny Purwaningsih; Ganda Setiawan (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study was conducted to analyze the effect of earnings per share, return on equity, price to book value, and total cash flow on stock prices in manufacturing companies in various industrial sectors. This study uses a type of causal comparative research which is used to determine the relationship between cause and effect on two or more variables. Sample in this study is manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange e for the period 2018-2020 using the purposive Sampling method. There are 14 companies that meet the research sample criteria, so sample is 42 financial statement data. Based on test results, it is known that simultaneously earnings per share, return on equity, price to book value, and total cash flow have a simultaneous effect on stock prices in various industrial sector manufacturing companies listed on the Indonesia Stock Exchange e in 2018-2020. The partial test results show earnings per share has a positive effect on stock prices, return on equity has no effect on stock prices, price to book value has a positive effect on stock prices, and total cash flow has a positive effect on stock prices.